Nutritional factors for anemia in pregnancy: A systematic review with meta-analysis - Zhang, Jing; Li, Quanhong; Song, Ying; Fang, Liping; Huang, Lei; Sun, Yu (Frontiers in Public Health, 2022)
Abstract Background: Anemia in pregnancy is a serious threat to maternal and child health and is a major public health problem. However, the risk factors associated with its incidence are unclear and controversial. Methods: PubMed, Ovid Embase, Web of Science, and Cochrane databases were systematically searched (inception to June 27, 2022). The screening of search results, extraction of relevant data, and evaluation of study quality were performed independently by two reviewers. Results: A total of 51 studies of high quality (NOS score ≥ 7) were included, including 42 cross-sectional studies, six case-control studies, and three cohort studies. Meta-analysis showed that infected parasite, history of malarial attack, tea/coffee after meals, meal frequency≤2 times per day, frequency of eating meat ≤ 1 time per week, frequency of eating vegetables ≤ 3 times per week, multiple pregnancies, multiparous, low household income, no antenatal care, rural residence, diet diversity score ≤ 3, have more than 3 children, history of menorrhagia, underweight, family size≥5, middle upper arm circumference＜23, second trimester, third trimester, birth interval≤ 2 year were all risk factors for anemia in pregnancy. Conclusions: Prevention of anemia in pregnancy is essential to promote maternal and child health. Sufficient attention should be paid to the above risk factors from the social level and pregnant women's own aspects to reduce the occurrence of anemia in pregnancy.